Values and preferences of medication use in patients for primary and secondary prevention of cardiovascular diseases: a mixed-methods exploratory study - Shenghan LI; Heyue DU; Kang AN; Longtao HE; Jing LI; Sheyu LI (Chinese General Practice Journal)
Background: Medication therapy is a cornerstone for the primary and secondary prevention of cardiovascular diseases, yet values and preferences regarding medication use remain unclear. Objective: To explore the values and preferences of medication use in patients for the primary and secondary prevention of cardiovascular diseases. Methods: This study explanatory sequential mixed methods study recruited patients for primary or secondary prevention of cardiovascular diseases at West China Hospital of Sichuan University and Yulin Community Health Service Center from November 2021 to January 2022. The focus group interviews collected the understanding of the values and preferences related to medication use among the participants. After coding with MAXQDA 2020, the investigators sorted, analyzed, and extracted the themes using Colaizzi's seven-step analysis method. Following the findings from the qualitative study, a quantitative survey was conducted from November 2022 to February 2023 among a conveniently sampled group of participants in multidisciplinary departments before the quantitative analysis. Results: The focus group interview included 21 participants, yielding four themes: (1) cognition and behavior towards medication; (2) barriers to medication use; (3) facilitators of medication use; and (4) needs for medical services. The quantitative survey collected 186 valid questionnaires (response rate: 93.5%), confirming common missed doses and medication stigma. Despite the heterogeneity in medication preferences, participants preferred fewer types of drugs and lower frequencies of medication and were averse to injectable formulations. Conclusion: The study suggests the preference of the compound preparations to reduce the number of pills and the integrity of the therapeutic regimens and daily lives to reduce the burden of taking medications for people receiving cardiovascular prevention. Timely identification and intervention targeting the individual-level misconceptions and improper practices are critical to improve the adherence.